Clinical practice of traditional Chinese medicines for chronic heart failure. Issue 1 (11th July 2010) - Fu, Shufei; Zhang, Junhua; Gao, Xiumei; Xia, Ye; Ferrelli, Rita; Fauci, Alice; Guerra, Ranieri; Hu, Limin
Abstract : Background: Chinese medicines have been used for chronic heart failure (CHF) for thousands of years; however, the status of traditional Chinese medicines (TCMs) used for CHF has not been reported. This review was carried out in the framework of a joint Sino-Italian Laboratory. Objective: To investigate the baseline of clinical practice of TCMs for CHF, and to provide valuable information for research and clinical practice. Methods: The authors included articles about the use of TCMs for the treatment of CHF by searching the Chinese Journal Full-text Database (1994 to November 2007). Results: In all, 1029 papers were included, with 239 herbs retrieved from these. The most commonly used herbs included Huangqi ( Radix Astragali ), Fuling ( Poria ), Danshen ( Radix Salviae Miltiorrhiae ), Fuzi ( Radix Aconiti Lateralis Preparata ) and Tinglizi ( Semen Lepidii ). Modern Chinese patent medicines (produced by pharmaceutical companies) and traditional prescriptions (comprising several herbs) are the application forms of these drugs. Shenmai, Shengmai and Astragalus injections were the most commonly used Chinese patent medicines. Some classic prescriptions (including Zhenwu decoction, Shengmai powder and Lingguizhugan decoction) were also frequently used. The effectiveness and safety of the TCMs were both satisfactory, and the traditional Chinese medicine and western medicine therapy could significantly improve the clinical effectiveness and reduce some of the adverse reactions from western medicines used alone. Conclusion: The authors have acquired overall information about the clinical application of TCMs for CHF. Modern pharmacology has provided limited evidence for the rationality of this clinical use. Further research is needed to provide more evidence.